2023
DOI: 10.1002/jts.22937
|View full text |Cite
|
Sign up to set email alerts
|

The mental health impact of the COVID‐19 pandemic and exposure to other potentially traumatic events up to old age

Abstract: We investigated whether the impact of potentially traumatic events (PTEs) on trauma‐related symptoms changes across the transitional adult lifespan (i.e., 16–100 years old) and if this association differs for self‐reported COVID‐19–related PTEs compared to other PTEs. A web‐based cross‐sectional study was conducted among 7,034 participants from 88 countries between late April and October 2020. Participants completed the Global Psychotrauma Screen (GPS), a self‐report questionnaire assessing trauma‐related symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
0
1
0
Order By: Relevance
“…Furthermore, it has been reported that the COVID-19 pandemic is likely to worsen pre-existing mental health conditions and may be involved in the emergence of new stress-related disorders for most people ( 9 ). The COVID-19 pandemic has been proposed to generate a higher and enduring proportion of traumatic symptoms than other potentially stressful events ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been reported that the COVID-19 pandemic is likely to worsen pre-existing mental health conditions and may be involved in the emergence of new stress-related disorders for most people ( 9 ). The COVID-19 pandemic has been proposed to generate a higher and enduring proportion of traumatic symptoms than other potentially stressful events ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Horesh and Brown ( 2020 ) concluded that COVID-19 should be viewed from the perspective of trauma because it will most certainly lead to stress-related mental health issues. In adults, COVID-19-related events have been shown to be associated with more severe trauma-related symptoms than other potentially traumatic events (Olff et al, 2021 ; Havermans et al, 2023 ). Structural dissociation of the personality (SDP) theory (Van Der Hart et al, 2004 ; van der Hart et al, 2006 ) and polyvagal theory (Porges, 2007 , 2022 ) may promote the conceptualization of COVID-19 pandemic-triggered dissociative disorders within a psychophysiological and neurophysiological framework.…”
Section: Introductionmentioning
confidence: 99%